Effects of BNN27, a novel C17-spiroepoxy steroid derivative, on experimental retinal detachment-induced photoreceptor cell death - Tsoka, Pavlina (Sci Rep, 2018)
Retinal detachment (RD) leads to photoreceptor cell death secondary to the physical separation of the retina from the underlying retinal pigment epithelium. Intensifying photoreceptor survival in the detached retina could be remarkably favorable for many retinopathies in which RD can be seen. BNN27, a blood-brain barrier (BBB)-permeable, C17-spiroepoxy derivative of dehydroepiandrosterone (DHEA) has shown promising neuroprotective activity through interaction with nerve growth factor receptors, TrkA and p75(NTR). Here, we administered BNN27 systemically in a murine model of RD. TUNEL(+) photoreceptors were significantly decreased 24 hours post injury after a single administration of 200 mg/kg BNN27. Furthermore, BNN27 increased inflammatory cell infiltration, as well as, two markers of gliosis 24 hours post RD. However, single or multiple doses of BNN27 were not able to protect the overall survival of photoreceptors 7 days post injury. Additionally, BNN27 did not induce the activation/phosphorylation of TrkA(Y490) in the detached retina although the mRNA levels of the receptor were increased in the photoreceptors post injury. Together, these findings, do not demonstrate neuroprotective activity of BNN27 in experimentally-induced RD. Further studies are needed in order to elucidate the paradox/contradiction of these results and the mechanism of action of BNN27 in this model of photoreceptor cell damage.